2006
DOI: 10.1245/aso.2006.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neoadjuvant Chemoradiation on Operative Mortality and Morbidity for Pancreaticoduodenectomy

Abstract: Neo-CRT does not increase the mortality or morbidity of PD. In contrast, neo-CRT was associated with a marked reduction in the incidence of pancreatic leak, as well as leak-associated morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 31 publications
6
27
0
1
Order By: Relevance
“…However, previous studies as well as this study have shown that NACRT is feasible and does not significantly interfere with the postoperative course [20,41]. Furthermore, NACRT may even bring beneficial effect on postoperative complications including pancreatic fistula [42,43]. Although there is no convincing evidence, NACRT may induce the atrophy and distortion of lobular structure with fibrotic change, thereby resulting in the reduction of pancreatic exocrine activity.…”
Section: Discussionmentioning
confidence: 65%
“…However, previous studies as well as this study have shown that NACRT is feasible and does not significantly interfere with the postoperative course [20,41]. Furthermore, NACRT may even bring beneficial effect on postoperative complications including pancreatic fistula [42,43]. Although there is no convincing evidence, NACRT may induce the atrophy and distortion of lobular structure with fibrotic change, thereby resulting in the reduction of pancreatic exocrine activity.…”
Section: Discussionmentioning
confidence: 65%
“…However, this effect did not persist as shown by an intrainstitutional comparison [15]. The effect of neoadjuvant CRT on mortality and morbidity for pancreaticoduodenectomy was recently analyzed retrospectively at the Duke University Medical Center comparing 79 patients resected after CRT and 67 patients without pretreatment [10]. Lethality rates were 3.8% and 4.5% in the respective groups and no increase in morbidity after CRT was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic leak rate refers to increased drain amylase levels (i.e., drain amylase levels threefold above the serum levels as previously published by our group). 4 Amylase levels were measured based on clinical suspicion for leak (e.g., increased in volume output, changes in consistency, color, etc.) or when the patient was started on regular diet.…”
Section: Methodsmentioning
confidence: 99%